2022
DOI: 10.3389/fcvm.2022.1052521
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the series of CYP2C9*non3 variants, an unignorable predictor of warfarin sensitivity in Chinese population

Abstract: BackgroundsGene polymorphisms are critical for variations in warfarin dose. To date, more than 70 CYP2C9 alleles have been identified. This study was designed to clarify the clinical significance of CYP2C9*non-3 variants to warfarin sensitivity in Chinese Han patients.MethodsThe entire CYP2C9 gene region was sequenced in 1,993 individuals, and clinical data and VKORC1 genotypes were collected from 986 patients with atrial fibrillation treated with warfarin. The SKAT-O method was used to analyze the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The CYP2C9*13 allele was rst reported in a Chinese population [14] and it occurs almost exclusively in East Asian populations [15]. In addition to CYP2C9*3, CYP2C9*13 is considered a relatively common allelic variant in East Asian populations, with an allele frequency of 0.16-0.7% [16][17][18][19]. In this study, the allele frequency of CYP2C9*13 was intermediate between CYP2C9*2 and CYP2C9*3.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The CYP2C9*13 allele was rst reported in a Chinese population [14] and it occurs almost exclusively in East Asian populations [15]. In addition to CYP2C9*3, CYP2C9*13 is considered a relatively common allelic variant in East Asian populations, with an allele frequency of 0.16-0.7% [16][17][18][19]. In this study, the allele frequency of CYP2C9*13 was intermediate between CYP2C9*2 and CYP2C9*3.…”
Section: Discussionmentioning
confidence: 74%
“…CYP2C9*13 was rst identi ed in the Han Chinese in 2004 [14] and has been found almost exclusively in East Asian populations [15]. In the Chinese population, CYP2C9*13 is a relatively common CYP2C9 variant other than CYP2C9*3, with a gene frequency of 0.16-0.7% [16][17][18][19]. Several in vivo and in vitro studies have demonstrated that CYP2C9*13 is associated with a lower drug metabolic activity than CYP2C9*1 [15,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Typical missense variant CYP2C9*3 caused a remarkable decrease in the S-warfarin clearance rate, leading to the increased risk of venous thromboembolism and bleeding in patients ( 13 ). Our recent studies revealed that a lot of rare CYP2C9 alleles are carried by Chinese individuals and most of missense mutations in CYP2C9 gene are highly related to the low dose of warfarin in Chinese population ( 18 , 20 , 34 ). In this study, we developed one time-saving and cost-effective genotyping method for CYP2C9 and performed a genetic screening in 1163 Chinese individuals.…”
Section: Discussionmentioning
confidence: 99%